Generic regimes of quantum many-body dynamics of trapped bosonic systems with strong repulsive interactions - Streltsova, Oksana I.; Alon, Ofir E.; Cederbaum, Lorenz S.; Streltsov, Alexej Iwanowitsch (Physical review. A, Atomic, molecular, and optical physics, 2014)
The nonequilibrium quantum dynamics of trapped bosons interacting by strong interparticle interaction of finite range in one, two, and three spatial dimensions is investigated on an accurate many-body level. We use different time-dependent processes to destabilize the systems' ground states: A sudden quench of the strength of the interparticle repulsion is accompanied by displacement of the trap. Two qualitatively different but otherwise generic dynamical quantum many-body behaviors are discovered. In the first, the overall “topology” of the ground-state density is preserved, whereas in the second the density totally “explodes.” An intuitive many-body time-dependent model is devised to interpret and explain the observations. The generality of the discovered scenarios is explicitly confirmed in traps of various shapes and dimensionality, and interparticle interactions of different forms and ranges. Implications are briefly discussed.
Gesehen am 23.07.2020